A Decade of Research on C9orf72 in Frontotemporal Dementia (2014-2024): A Bibliometric Analysis of Global Trends and Hotspots - He, Miao; Zeng, Sheng; Tang, Zhenchu; Qin, Lixia; Yan, Weiqian; Wang, Chunyu; Zhang, Hainan; Chen, Zhao; Long, Zhe (Current Neuropharmacology, 2025)
<span class=
Keywords: C9orf72